(untitled) (Metallurgy and Foundry Engineering, 2016)
The AZ91 magnesium alloy was processed up to 87.5% of total thickness reduction in several thermodynamic routes, consisted of hot rolling and intermediate annealing. The hot-rolling process was performed at a high strain rate equal to 1.6 s−1 and at a temperature of 430°C. The intermediate annealing was performed at 430°C for 15 minutes after each route. It was found that, during hot rolling, the hardness of the material increased from 32 HV to 40 HV, and the structure investigations showed a huge amount of twins formed inside the grains (which were not observed after annealing). Tensile tests have shown strong anisotropy in mechanical properties of the “as-rolled” samples dependent on the orientation between tension direction (TD) and rolling direction (RD). The samples with TD perpendicular to RD proved higher ultimate tensile strength (UTS) and (on the other hand) worse plastic properties as compared to the samples with TD parallel to RD. The annealing has an effect on the reduction of mechanical properties anisotropy. X-ray investigations have shown texture changes from the basal type with the additional (0001) <1120> component for “as-rolled” samples to the texture with the main (0001) <1010> component for annealed samples. The texture changes had a great impact on the anisotropy of mechanical properties of the investigated AZ91 magnesium alloy.